Análise de dados sobre crianças com excesso de peso com auxílio de recursos computacionais - Bueno, Camilo Antonio Monteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Childhood obesity has reached worrying rates in the Brazilian population; its occurrence has acquired great significance in the health field. Thus, in addition to the diagnosis of the obesity in children, other factors involved with its emergence should be investigated. The process of identification and analysis of these factors has proven to be a very complex task - the great number of studies published on this subject, many of them inconclusive, is an evidence of this complexity. This master thesis aimed to analyze data on children, especially overweight ones, in order to establish hypotheses on the role of some factors that may be involved with childhood obesity. Among the analyzed factors, some have been cited in the literature as possibly related to the emergence of the childhood obesity, namely, the delivery method, the infant weight at birth, the period of breastfeeding and the number of daily hours of sleep, in addition to the obesity hereditary. The factor pregnancy period was also included in the analysis. A second objective of this study was to test and evaluate the application of the association technique, from the data mining area, together with the database resource, as an auxiliary tool in the analysis process specially on the data types that are of interest in this work. In order to achieve the intended objectives, a set of data involving 107 children between 6 and 13 years old was analyzed. The data was collected in the city of Marília - SP and it consists of 38 normal weight children, 38 obese ones and 31 overweight ones. The data analysis process allowed to identify some relevant correlations between variables involved in the problem and establish hypotheses to be analyzed in more details. Regarding the used computational resources, association rules seem to be quite interesting for the analysis of the types of data considered in this study, since they allow to establish hypotheses from the correlations found between ...

A obesidade infantil tem se tornado uma preocupação crescente na área da saúde devido às possíveis consequências que ela pode trazer a um indivíduo, tanto na sua infância quanto na fase adulta. Assim, além do diagnóstico da obesidade em crianças, devem ser investigados fatores que podem estar envolvidos com o seu surgimento. O processo de identificação e análise destes fatores tem se mostrado uma tarefa bastante complexa - a grande quantidade de estudos que tem sido publicada sobre o tema, muitos deles inconclusivos, é uma mostra disso. Este trabalho de mestrado teve o objetivo de analisar dados sobre crianças, em particular, com excesso de peso, visando levantar hipóteses quanto à possível influência de alguns fatores para o surgimento da obesidade infantil. Dentre os fatores analisados, alguns têm sido citados na literatura como possivelmente relacionados ao surgimento da obesidade infantil, a saber, o tipo de parto, o peso da criança ao nascer, o tempo de aleitamento materno e a quantidade de horas de sono diárias da criança, além da hereditariedade para a obesidade. Também foi incluído nas análises o fator tempo de gestação. Um segundo objetivo deste estudo foi testar e avaliar a viabilidade de uso da técnica de associação, da área de mineração de dados, em associação com o recurso banco de dados, como ferramenta auxiliar no processo de análise especificamente dos tipos de dado de interesse neste trabalho. Para atingir os objetivos pretendidos, foi analisado um conjunto de dados referentes a 107 crianças entre 6 e 13 anos, coletado na cidade de Marília - SP, constituído de: 38 eutróficas, 38 obesas e 31 com sobrepeso. O processo de análise dos dados possibilitou identificar correlações relevantes entre variáveis envolvidas no problema, a partir das quais pôde-se levantar algumas hipóteses, como a de que o parto cesárea, em especial, e o tempo de aleitamento materno não adequado poderiam...
Keywords: Nutrition; Nutrição; Obesidade nas crianças; Mineração de dados (Computação)